PEMBAGIAN WARISAN TERHADAP PERKAWINAN POLIGAMI TINJAUAN PERUNDANG-UNDANGAN DI INDONESIA - Susi Kusmawaningsih; Chairul Musthopa (Program Studi Hukum Keluarga Islam, Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2024)
Polygamy is a form of marriage that is limitedly recognized in the Indonesian legal system, especially for Muslims. In the context of inheritance distribution, polygamous marriages often cause conflict due to complex family structures. This article discusses the distribution of inheritance in polygamous marriages according to Islamic law and legislation in Indonesia, especially Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). The distribution of inheritance in polygamous marriages in Indonesia is a complex legal issue and often causes conflict in society. This article analyzes the problem of inheritance distribution in polygamous marriages based on applicable legislation, especially the Compilation of Islamic Law (KHI) as the main guideline. In Islamic law, all wives and children have fair inheritance rights, but its implementation is often hampered by a lack of understanding of the law, the dominance of custom, and the lack of documentation of assets by the testator. This article also discusses various practical obstacles that occur in society, such as lack of understanding of the law, conflict between wives, discrimination against children from certain wives, and the influence of customs that conflict with sharia. To overcome these problems, it is recommended to have transparent asset recording, making wills according to Islamic law, legal education for the community, and the role of religious courts in resolving inheritance disputes. Through a normative approach, this article analyzes legal regulations, implementation challenges, and solutions that can be applied to overcome the problem of inheritance distribution in polygamous families. The results of the study show that although the law has regulated the distribution of inheritance in detail, conflicts often arise due to inconsistencies in practices in the field. Therefore, a deep understanding and harmonization of legal and customary regulations are needed to ensure justice for all parties. The results and discussion of this article emphasize the importance of synergy between Islamic law, national legislation, and social approaches to create justice in the distribution of inheritance in polygamous marriages. With preventive measures and appropriate resolutions, inheritance conflicts can be minimized, so that the rights of heirs are protected and the value of justice in Islamic law can be realized effectively in Indonesia. Poligami merupakan bentuk perkawinan yang diakui secara terbatas dalam sistem hukum Indonesia, khususnya bagi umat Islam. Dalam konteks pembagian warisan, perkawinan poligami sering kali menimbulkan konflik akibat struktur keluarga yang kompleks. Artikel ini membahas pembagian warisan dalam perkawinan poligami menurut hukum Islam dan perundang-undangan di Indonesia, khususnya Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Kompilasi Hukum Islam (KHI). Pembagian warisan dalam perkawinan poligami di Indonesia merupakan isu hukum yang kompleks dan sering kali menimbulkan konflik di tengah masyarakat. Artikel ini menganalisis permasalahan pembagian warisan dalam perkawinan poligami berdasarkan perundang-undangan yang berlaku, terutama Kompilasi Hukum Islam (KHI) sebagai pedoman utama. Dalam hukum Islam, semua istri dan anak memiliki hak waris yang adil, namun implementasinya sering kali terkendala oleh minimnya pemahaman hukum, dominasi adat, dan kurangnya dokumentasi harta oleh pewaris. Artikel ini juga membahas berbagai kendala praktis yang terjadi di masyarakat, seperti ketidakpahaman tentang hukum, konflik antaristri, diskriminasi terhadap anak dari istri tertentu, serta pengaruh adat yang bertentangan dengan syariat. Untuk mengatasi masalah tersebut, disarankan adanya pencatatan harta secara transparan, pembuatan wasiat sesuai hukum Islam, edukasi hukum kepada masyarakat, dan peran pengadilan agama dalam penyelesaian sengketa waris. Melalui pendekatan normatif, artikel ini menganalisis aturan hukum, tantangan implementasi, serta solusi yang dapat diterapkan untuk mengatasi permasalahan pembagian warisan dalam keluarga poligami. Hasil kajian menunjukkan bahwa meskipun hukum telah mengatur pembagian warisan secara rinci, konflik kerap muncul akibat ketidaksesuaian praktik di lapangan. Oleh karena itu, diperlukan pemahaman yang mendalam dan harmonisasi antara aturan hukum serta adat untuk memastikan keadilan bagi semua pihak. Hasil dan Pembahasan dari artikel ini menegaskan pentingnya sinergi antara hukum Islam, perundang-undangan nasional, dan pendekatan sosial untuk menciptakan keadilan dalam pembagian warisan dalam perkawinan poligami. Dengan langkah-langkah preventif dan penyelesaian yang tepat, konflik warisan dapat diminimalkan, sehingga hak-hak ahli waris terlindungi dan nilai keadilan dalam syariat Islam dapat terwujud secara efektif di Indonesia.